Selection of non-conventional machining processes using the OCRA method - Madić, Miloš; Petković, Dušan; Radovanović, Miroslav (Serbian Journal of Management, 2015)
Selection of the most suitable nonconventional machining process (NCMP) for a given machining application can be viewed as multi-criteria decision making problem with many conflicting and diverse criteria. To aid these selection processes, different multi-criteria decision making (MCDM) methods have been proposed. This paper introduces the use of an almost unexplored MCDM method, i.e. operational competitiveness ratings analysis (OCRA) method for solving the NCMP selection problems. Applicability, suitability and computational procedure of OCRA method have been demonstrated while solving three case studies dealing with selection of the most suitable NCMP. In each case study the obtained rankings were compared with those derived by the past researchers using different MCDM methods. The results obtained using the OCRA method have good correlation with those derived by the past researchers which validate the usefulness of this method while solving complex NCMP selection problems.